2016
DOI: 10.3138/cpp.2016-006
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Confidence in Police Creates a “Blue Ceiling” for Sex Workers' Safety

Abstract: Confidence in the police is fundamental to citizens' willingness to report unlawful behaviour, share intelligence about crime, seek help when victimized, and generally comply with the law. Marginalized groups overwhelmingly report a lack of confidence that police will apply the law fairly. Although sex work research reports a wide range of negative experiences with the police, it is not known how common these experiences are because most research focuses solely on street-based sex workers and does not include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 38 publications
1
73
0
1
Order By: Relevance
“…As reported in our previous analyses (Benoit et al 2016a;Benoit et al 2016b), sex workers in this sample reported higher unmet health care needs (40.4% vs. 14.9% with unmet needs) and have significantly lower levels of confidence in the police (63% vs. 15% report 'not very much' or 'no confidence at all' in the police) compared to other Canadians. This prior research noted that stigma, discrimination and criminalization all likely factored in to these poor outcomes for sex workers.…”
Section: Demographic Profilesupporting
confidence: 53%
See 1 more Smart Citation
“…As reported in our previous analyses (Benoit et al 2016a;Benoit et al 2016b), sex workers in this sample reported higher unmet health care needs (40.4% vs. 14.9% with unmet needs) and have significantly lower levels of confidence in the police (63% vs. 15% report 'not very much' or 'no confidence at all' in the police) compared to other Canadians. This prior research noted that stigma, discrimination and criminalization all likely factored in to these poor outcomes for sex workers.…”
Section: Demographic Profilesupporting
confidence: 53%
“…Nearly half of our participants had a well-thought-out view on prostitution legal reform and the vast majority favored change in the direction of decriminalization and regulation by utilizing Canada's existing occupational health and safety laws that regulate other service jobs. As hinted at above and discussed in detail elsewhere (Benoit et al 2016b), sex workers in our multi-city study had significantly lower confidence in police than other Canadians, and said that the police especially do a poor job treating sex workers fairly and being approachable and easy to for them to talk to. Decriminalization and regulation may not completely eliminate such prejudicial attitudes and unjust treatment of sex workers by police, but at least some of our participants suggested legal reform may reduce hesitancy by sex workers to involve the police if they witness or experience a crime (Abel et al 2009;Stoltz et al 2007;O'Doherty 2011;Abel et al 2010).…”
Section: Discussionmentioning
confidence: 89%
“…In India, some brothel owners paid police to avoid raids, or allowed pre-selected sex workers to be arrested [99]. Police harassment, raids [35,110,120], undercover operations, entrapment, and pressure to act as informants [97,128] generated fear, anxiety, and stress, with media sometimes publicising sex workers’ faces during raids [120].…”
Section: Resultsmentioning
confidence: 99%
“…Studies showed that policing practices in contexts of criminalisation and regulation institutionalised violence against sex workers, both directly through police inflicting physical or sexual violence or demanding fines in lieu of arrest, and indirectly by restricting access to justice and thus creating an environment of impunity for perpetrators of violence [97,102,122,125,127130].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation